New potentials in biomedical application of hydrated electrons: A functional and biomedical effects study of an electromagnetic base liquid containing hydrated electrons - Zhuangbin Zheng; Fanlei Ran; Lushan Liang; Yiqian Zhang; Xianwen Li; Liqun Zhang; Lijun Bi (PLoS ONE, 2025)
Hydrated electrons (e aq - ) are widely studied in pollutant degradation owing to their high reducing power. Recent studies indicate that transiently generated e aq - during radiotherapy can enhance chemotherapeutic antitumor effects via reduction activity. However, biomedical applications remain limited because conventional methods generate e aq - in situ and are short-lived, precluding storage. In this study, we present a storable electromagnetic base liquid (EBL), reference-linked to prior preparation work, and analyze its physicochemical and organism-level effects. The EBL showed strong alkalinity (pH 13.08), low oxidation-reduction potential (ORP 47.1 mV), and a total antioxidant capacity of 1.6 mM Trolox equivalents antioxidant capacity. Using a larva zebrafish ( Danio rerio ) digital phenotyping platform, we identified a non-adverse concentration and generated unbiased predictions clustering EBL with antitumor, uric acid-lowering, and hypoglycemic drugs. These findings motivate further biological investigation of EBL’s biomedical potential and provide a basis for subsequent validation.